The Technical Feasibility of Organic Sheet Mulch From Palm Fiber Waste - Muhamad Arip (Politeknik Pembangunan Pertanian Malang, 2022)
Sugar palm is a multi-purpose plant that can be processed into various products when it is 15 years old. Palm plants are no longer productive but still contain starch in the stems, generally, they are cut down and further processed into palm starch flour. Palm flour production activities produce liquid waste and solid waste. The waste generated to produce 1.7 tons of palm starch flour is 4.3 tons. Liquid waste is discharged directly into the river. Meanwhile, solid waste is allowed to accumulate around the palm starch processing factory, which pollutes the surrounding environment, so managing waste from processing palm starch is necessary. An alternative to utilizing palm fibre waste is to process it into sheet organic mulch as a soil cover medium in plant cultivation activities. Sheet organic mulch that is widely available today is made from coco fibre. Sheet organic mulch can be made with several organic adhesives, namely latex, clay, palm flour and tapioca flour. Sheet organic mulch from palm fibre waste requires technical testing to determine which adhesive can produce high-quality mulch. Based on the tensile test results, it was found that the organic mulch of palm fibre with latex adhesive had the most similar technical properties to organic mulch on the market. Keywords— Palm Fibre, Feasibility, Organic Mulch